Salicylate enhances the response of prostate cancer to radiotherapy. Issue 5 (4th January 2019) - Broadfield, Lindsay A.; Marcinko, Katarina; Tsakiridis, Evangelia; Zacharidis, Panayiotis G.; Villani, Linda; Lally, James S. V.; Menjolian, Gabe; Maharaj, Danitra; Mathurin, Tammy; Smoke, Marcia; Farrell, Thomas; Muti, Paola; et al.
Abstract : Background: Radiotherapy (RT) is a key therapeutic modality for prostate cancer (PrCa), but RT resistance necessitates dose‐escalation, often causing bladder and rectal toxicity. Aspirin, a prodrug of salicylate (SAL), has been associated with improved RT response in clinical PrCa cases, but the potential mechanism mediating this effect is unknown. SAL activates the metabolic stress sensor AMP‐activated protein kinase (AMPK), which inhibits de novo lipogenesis, and protein synthesis via inhibition of Acetyl‐CoA Carboxylase (ACC), and the mammalian Target of Rapamycin (mTOR), respectively. RT also activates AMPK through a mechanism distinctly different from SAL. Therefore, combining these two therapies may have synergistic effects on suppressing PrCa. Here, we examined the potential of SAL to enhance the response of human PrCa cells and tumors to RT. Methods: Androgen‐insensitive (PC3) and ‐sensitive (LNCaP) PrCa cells were subjected to proliferation and clonogenic survival assays after treatment with clinically relevant doses of SAL and RT. Balb/c nude mice with PC3 xenografts were fed standard chow diet or chow diet supplemented with 2.5 g/kg salsalate (SAL pro‐drug dimer) one week prior to a single dose of 0 or 10 Gy RT. Immunoblotting analysis of signaling events in the DNA repair and AMPK‐mTOR pathways and lipogenesis were assessed in cells treated with SAL and RT. Results: SAL inhibited proliferation and clonogenic survival in PrCa cells and enhanced the inhibition mediated by RT. Salsalate, added to diet, enhanced the anti‐tumor effects of RT in PC3 tumor xenografts. RT activated genotoxic stress markers and the activity of mTOR pathway and AMPK and mediated inhibitory phosphorylation of ACC. Interestingly, SAL enhanced the effects of RT on AMPK and ACC but blocked markers of mTOR activation. Conclusions: Our results show that SAL can enhance RT responses in PrCa. Salsalate is a promising agent to investigate this concept in prospective clinical trials of PrCa in combination with RT.